Cynosurus peltieri (Pooideae, Poaceae), a poorly known species endemic to the Algerian-Tunisian terrestrial flora: further insights on its occurrence, IUCN Red List assessment, and lectotypification - El Mokni, Ridha; Verloove, Filip (Phytotaxa, 2022)
Cynosurus peltieri (Poaceae) is a very poorly known species only occurring in Algeria and Tunisia. A morphological description, together with its distribution and habitat, taxonomy, and IUCN Red List assessment are provided in the present paper. Photographic illustrations of the species comparing it with the similar Cynosurus polybracteatus, together with an updated diagnostic key to the Cynosurus species in North Africa, are also provided. In addition, the name is lectotypified on a specimen preserved at MPU, with isolectotypes preserved at P and BC.